Pengembangan dan Pembinaan Karir Guru di bidang Pendidikan Kejuruan - Ritonga, Abdul Kadir (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The article is entitled the development of teacher careers in the field of vocational education. Vocational education aims to improve intelligence, knowledge, personality, noble character, and skills of students to live independently and participate in further education in accordance with the vocational program.The purpose of vocational education implies that vocational education prepares a professional workforce and also prepares students to be able to continue their education to a higher level or areas expertise. Data research is collected from some books and scientific articles referred to the research. Career development refers to the process of the developing values, skills, talents, interests, personality characteristic, and lifelong knowledge of the world of work. The role of the teacher is very important so that the development of a teacher’s career must be considered by the parties concerned for the advancement of education, especially vocational education in Indonesia.